Defining antibiotic dosing in lung infections - Jamal, Jannatul-Ain; Abdul Aziz, Mohd. Hafiz; Lipman, Jeffrey; Roberts, Jason A. (Lippincott Williams & Wilkins, 2013)
Defining optimal antibiotic dosing for treatment of lung infections is challenging because of the interrelationship between patient characteristics (eg, pathophysiological changes of lung during an infection, albumin level, renal function), antibiotic characteristics (eg, physicochemical properties, protein binding), and bacterial pathogen susceptibility. Measurement of antibiotic concentration in the lung compartments, such as epithelial lining fluid (ELF), is important to describe the drug exposure at site of infection. This article reviews published data on antibiotic penetration described by the ELF to plasma (ELF:plasma) ratios and the probability of pharmacokinetic/pharmacodynamics (PK/PD) attainment at the target site with current dosing regimens to outline dosing strategies that could optimize the PK/PD indices. Antibiotic physicochemical properties could be used to predict the extent of penetration into the lung tissues. Lipophilic antibiotics penetrate well into the lung compartments; however, standard dosing regimens generally seem to be insufficient to achieve optimal PK/PD indices in the ELF, particularly during severe infections. Aggressive dosing regimens are required for antibiotics that poorly or moderately penetrate the lung tissues, whereas nebulization could be the alternative method to enhance antibiotic concentration at the target site. Special populations such as the critically ill, patients on renal replacement therapy, and those with renal impairment need dosing to be individualized, as these populations have high PK variability. Dosing based on free drug concentrations should be considered preferred, as these concentrations frequently reflect the antibiotic concentration at the target site. Therefore, the use of therapeutic drug monitoring should be considered necessary, whenever possible, to guide dosing in lung infection.